Quantitative Study of Antibiotic Use in Urinary Tract Infection Patients at RSU X in East Jakarta 2019 - Hasan, Delina; Yardi, Yardi; Amalia, Rosa (Jurnal Health Sains, 2023)
Urinary tract infection is a health problem that can increase morbidity and even increase the death rate both in Indonesia and in the world. Urinary tract infection is the second most common infectious disease after upper respiratory tract infection which in its treatment must use antibiotic therapy, so the treatment must be appropriate and rational. The purpose of this study was to determine the use of antibiotics quantitatively using the ATC/DDD and 90% DU methods in patients with urinary tract infections at RSU X in East Jakarta. Methods, This research is a descriptive study using a cross-sectional design. Data collection was carried out retrospectively through the medical records of urinary tract infection patients at RSU X in East Jakarta in 2019, data analysis was carried out using the ATC/DDD method and DU 90%, sample size was 115 urinary tract infection patients who met the inclusion and exclusion criteria. The results showed that the total DDD/100 patient-days in this study was 96.65% with the highest type of antibiotic, namely levofloxacin, 44.07% DDD/100 patient-days. Drugs included in the DU segment 90% were levofloxacin (45.60%), ceftriaxone (21.54%), cefoperazone (11.33%), and amoxicillin clavulanate (9.00%).